Visualization of partial discharge burning voltage mechanism oncontaminated surfaces - Shwehdi, M.H. (1997)
This paper presents a new visualization of the pre-flashover phase burning discharge and proposes a mathematical model which may describe the burning partial discharge mechanism phase. It also introduces the results of an experimental model simulation, carried at the KFUPM High Voltage Laboratory under AC voltages, to visualize the burning discharge voltage and its variation with different contaminated surfaces